2020
DOI: 10.1002/sia.6857
|View full text |Cite
|
Sign up to set email alerts
|

In‐depth analysis of InAlN/GaN HEMT heterostructure after annealing using angle‐resolved X‐ray photoelectron spectroscopy

Abstract: During high-electron-mobility transistor elaboration process, a thermal treatment of In 0.2 Al 0.8 N (InAlN) barrier layer is performed in order to improve electrical performances. We showed previously that In 0.2 Al 0.8 N/GaN heterostructures, annealed at 850 C under O 2 partial pressure, present a specific in-depth organization. Angleresolved X-ray photoelectron spectroscopy is a powerful tool to precisely determine the spatial localization and relative position of the different interfaces, from InAlN until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The decrease in the N concentration at the top of the remaining InAlN layer (see Figure 3b) suggests the formation of N vacancies within the Wurtzite structure, which is consistent with previous X-ray photoelectron spectroscopy studies. [12,30] The presence of N vacancies below the original InAlN surface likely causes a reduction in the spontaneous polarization within the Wurtzite structure. [31] Eickelkamp and coworkers showed that annealing of a 12 nm-thick InAlN film for 2 min at 800 C degrades the carrier concentration and mobility in the 2DEG at the InAlN/GaN interface.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in the N concentration at the top of the remaining InAlN layer (see Figure 3b) suggests the formation of N vacancies within the Wurtzite structure, which is consistent with previous X-ray photoelectron spectroscopy studies. [12,30] The presence of N vacancies below the original InAlN surface likely causes a reduction in the spontaneous polarization within the Wurtzite structure. [31] Eickelkamp and coworkers showed that annealing of a 12 nm-thick InAlN film for 2 min at 800 C degrades the carrier concentration and mobility in the 2DEG at the InAlN/GaN interface.…”
Section: Discussionmentioning
confidence: 99%